Relay coordination analysis and protection solutions for smart grid distribution systems - Turan, Mehmet Tan; Gokalp, Erdin (Tubitak Scientific & Technological Research Council Turkey, 2016)
Growing complexity of conventional power grids and their management, increasing power demand and energy quality expectations considering grid reliability, and efficiency and security concerns have triggered the evolution of smart grids. This is an expected result of implementing new technologies in existing grids, including renewable sources such as wind turbines and photovoltaic modules. With implementation of such new elements to the system, the protection concept should be considered by system regulators. In order to analyze protection problems, simulation-based analysis should be carried out before high-cost experimental studies. In this study, a simulation-based evaluation for a smart grid based distribution system is performed. System simulations are realized considering different fault cases and optimum operating conditions are obtained. A ring grid is designed including a generator and a wind turbine as sources and variable loads as consumers. Several points in the grid are selected as fault locations, and the condition of connecting distributed generation plants to the grid is evaluated in the MATLAB/Simulink environment. This study presents an analysis about the possibility of forming a grid with high reliability and efficiency under fault conditions.
Keywords: Relay coordination; smart grid; overcurrent protection; short-circuit protection; Computer Science; Engineering